2022
DOI: 10.1021/acs.iecr.2c01640
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study and Model Assessment for n-Butyl Levulinate Production from Alcoholysis of 5-(Hydroxymethyl)furfural over Amberlite IR-120

Abstract: Alkyl levulinates such as n-butyl levulinate (BL) can play an important role in the fuel sector. Classically, BL is produced from the esterification of levulinic acid, but the butanolysis (or alcoholysis) of sugars requires less stages. The industrialization of this process requires the development of process flow diagrams and thus the knowledge of reaction kinetics and thermodynamics. To the best of our knowledge, there are no kinetic models for the production of BL from sugar butanolysis over heterogeneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Di Meno Di Buchianico et al [ 14 ] found that the reaction pathway displayed in Figure 1 was the most reliable. They assessed different models for the solvolysis of fructose to BL over Amberlite IR‐120 in an autoclave.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Di Meno Di Buchianico et al [ 14 ] found that the reaction pathway displayed in Figure 1 was the most reliable. They assessed different models for the solvolysis of fructose to BL over Amberlite IR‐120 in an autoclave.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The previous article mentioned that the following species concentrations were used as observables: 5‐HMF, BMF, LA, BL, and BF. [ 14 ] Thus, different levels of noise were added to these species concentrations.…”
Section: Errorsmentioning
confidence: 99%
See 3 more Smart Citations